Secure Location-Aided Routing Protocols With Wi-Fi Direct For Vehicular Ad Hoc Networks - Saleh, Ma'en; Dong, Liang; Aljaafreh, Ahmad; Al-Oudat, Naeem (International Journal of Communication Networks and Information Security (IJCNIS), 2022)
Secure routing protocols are proposed for the vehicular ad hoc networks. The protocolsintegrate the security authentication process with the Location-Aided Routing (LAR) protocol to supportWi-Fi Direct communications between the vehicles. The methods are robust against various security threats.The security authentication process adopts a modified Diffie-Hellman key agreement protocol. The Diffie-Hellman protocol is used with a short authentication string (SAS)-based key agreement over Wi-Fi Directout-of-band communication channels. It protects the communication from any man-in-the-middle securitythreats. In particular, the security process is integrated into two LAR routing schemes, i.e., the request-zoneLAR scheme and the distance-based LAR scheme.We conduct extensive simulations with different networkparameters such as the vehicular node density, the number of the malicious nodes, and the speed of thenodes. Simulation results show that the proposed routing protocols provide superior performance in securedata delivery and average total packet delay. Also, the secure distance-based LAR protocol outperforms thesecure request-zone LAR protocol.